Helmintoses intestinais: o processo de comunicação e informação no Programa de Educação e Saúde em Verminose Intestinal Helminthiasis: the process of communication and information in a Health Education Program on Intestinal Worms - Dalva A. Mello; Elisete S. Pedrazzani; Clemência P. Pizzigatti (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1992)
No trabalho sobre intervenção em helmintoses intestinais, no subdistrito de Santa Eudóxia (São Carlos, São Paulo), foi conduzido um processo de comunicação com o objetivo de ilustrar, demonstrar e consolidar a informação sobre o programa junto à comunidade. A comunicação desenvolveu-se ao longo da seqüência de eventos que ocorreram durante o desenvolvimento do trabalho de intervenção, veiculando e disseminando informação associada à participação da comunidade. This paper provides a framework for analysis of the effectiveness of the communication process used in the Health Promotion Program implemmented in two schools in the town of Santa Eudóxia (state of São Paulo), as well as in one of the Education and Health workshops. The materials were produced in cooperation with the local community and include folders, manuals, murals, panels and illustrative drawings. One of the most significant aspects of the communication process was the identification of the mother as the principal health promoter in the family. The results showed that the techniques and methods were appropriate to the needs of the people and may be used as a pedagogic instrument in developing health programs.